2022
DOI: 10.1002/clc.23821
|View full text |Cite
|
Sign up to set email alerts
|

Heart Team risk assessment with angiography‐derived fractional flow reserve determining the optimal revascularization strategy in patients with multivessel disease: Trial design and rationale for the DECISION QFR randomized trial

Abstract: In patients with multivessel disease (MVD), functional information on lesions improves the prognostic capability of the SYNTAX score. Quantitative flow ratio (QFR®) is an angiography‐derived fractional flow reserve (FFR) that does not require a pressure wire or pharmacological hyperemia. We aimed to investigate the feasibility of QFR‐based patient information in Heart Teams' discussions to determine the optimal revascularization strategy for patients with MVD. We hypothesized that there is an acceptable agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Online measurements, while the patient is still in the cath lab, usually do not have such a limitation. Finally, the potential role of QFR in heart team decisions is being investigated in ongoing DECISION QFR randomized trial ( 51 ).…”
Section: Limitations Of Fractional Flow Reserve Derived From Invasive...mentioning
confidence: 99%
“…Online measurements, while the patient is still in the cath lab, usually do not have such a limitation. Finally, the potential role of QFR in heart team decisions is being investigated in ongoing DECISION QFR randomized trial ( 51 ).…”
Section: Limitations Of Fractional Flow Reserve Derived From Invasive...mentioning
confidence: 99%
“…These elements have been leveraged in the multi-center FAVOR trials which remain in longer-term follow-up but have shown promising early results in guiding PCI ( 21 , 22 ). The ease of performing QFR also lends itself to strategy trials such as DECISION-QFR which is evaluating the agreement of a Heart Team discussion using QFR-based information compared with FFR-based information ( 23 ). Further studies could trial a precision-based strategy to conduit choice—for example, vessels with a QFR ≤0.80 would receive arterial conduit and those with QFR >0.80 would receive venous conduit—compared with standard of care.…”
mentioning
confidence: 99%